Deterrence through word of mouth - Johannes Rincke; Christian Traxler (Max Planck Institute for Research on Collective Goods, 2009)
The deterrent effect of law enforcement rests on the link between the actual and the perceived detection risk. We study the role of word of mouth for this linkage. Our approach makes use of micro data on compliance with TV license fees allowing us to distinguish between households who have been subject to enforcement and those who have not. Exploiting local variation in field inspectors' efforts induced by snowfall, we find a striking response of households to increased enforcement in their vicinity, with compliance rising significantly among those who had no interaction with inspectors. As we can exclude other channels of information transmission, our finding establishes a substantial deterrent effect mediated by word of mouth.
Keywords: K42; D83; 330; Deterrence; Law enforcement; Word of mouth; Normbefolgung; Rechtsdurchsetzung; Virales Marketing; Rundfunkfinanzierung; Österreich